2018
DOI: 10.1002/mrc.4705
|View full text |Cite
|
Sign up to set email alerts
|

Compressed NMR: Combining compressive sampling and pure shift NMR techniques

Abstract: Historically, the resolution of multidimensional nuclear magnetic resonance (NMR) has been orders of magnitude lower than the intrinsic resolution that NMR spectrometers are capable of producing. The slowness of Nyquist sampling as well as the existence of signals as multiplets instead of singlets have been two of the main reasons for this underperformance. Fortunately, two compressive techniques have appeared that can overcome these limitations. Compressive sensing, also known as compressed sampling (CS), avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…This is not clear using standard 1 H NMR techniques, as in Figure a, but it is revealed when removing the proton multiplicity using pure shift techniques , (Figure b) alongside variable temperature studies (Figure ). , Most of the carbon signals are also duplicated, although a few appear not to be. However, acquisition of an ultrahigh resolution 1 H– 13 C HSQC spectrum (Figure ) using recent compressive sampling techniques , confirmed that the duplicated signals have almost the same chemical shift.…”
Section: Resultsmentioning
confidence: 99%
“…This is not clear using standard 1 H NMR techniques, as in Figure a, but it is revealed when removing the proton multiplicity using pure shift techniques , (Figure b) alongside variable temperature studies (Figure ). , Most of the carbon signals are also duplicated, although a few appear not to be. However, acquisition of an ultrahigh resolution 1 H– 13 C HSQC spectrum (Figure ) using recent compressive sampling techniques , confirmed that the duplicated signals have almost the same chemical shift.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation from Figure 1 shows this effect. The fact that PS-NMR naturally fits to the compressed sensing reconstruction has been discussed extensively by Aguilar and coworkers [35]. Importantly, while the couplings between nuclei of the same kind (i.e., homonuclear) can be removed using selective echo pulse sequence block in both direct and indirect dimensions of an NMR spectrum, the pseudo-random NUS is feasible only in the latter case.…”
Section: Lesson 1: Reduce the Number Of Peaksmentioning
confidence: 99%
“…[18][19][20][21] A detailed account of this method can be found elsewhere. 22 Here it was possible, using this approach, to reduce the acquisition time of the 1 H- 13 C HSQC experiment (1024 increments, 2 transients per increment, 14 Hz/point) employed for the analysis of HManA and HGulA from around 80 minutes to 10 minutes. As an example, Figure 4 shows a comparison between a traditionally-acquired 1 H- 13 C HSQC (10 min) of HManA at pD 3.4, and the same experiment acquired using compressive sampling (also 10 min).…”
Section: Figurementioning
confidence: 99%